Penerapan Digital Marketing Sebagai Strategi Pemasaran UMKM - Robby Aditya; R Yuniardi Rusdianto (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2023)
Snack-producing, buying, and selling micro, small, and medium enterprises (MSMEs) in Surabaya are the partners in this community service project. In the city of Surabaya, MSMEs that have transformed into Community Service Partners have been around for almost a decade. However, there is still a lot of work to be done in the digital space for its marketing efforts. As a result, these MSMEs receive assistance in enhancing their marketing system with the assistance of digital marketing in order to support improved sales activities and expand their business objectives. Additionally, assistance with marketing their products through digital media accounts is provided to MSMEs. Instagram and Tiktok, in addition to digital media administration.